1988
DOI: 10.1152/ajpendo.1988.255.2.e166
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between glutamine concentration and protein synthesis in rat skeletal muscle

Abstract: Muscle glutamine concentration ([GLN]) and protein synthesis rate (Ks) have been examined in vivo in well-fed, protein-deficient, starved, and endotoxemic rats. With protein deficiency (8 or 5% casein diet), [GLN] fell from 7.70 to 5.58 and 3.56 mmol/kg in the 8 and 5% diet groups, with Ks falling from 15.42 to 9.1 and 6.84%/day. Three-day starvation reduced [GLN] and Ks to 2.38 mmol/kg and 5.6%/day, respectively. In all these groups food intakes and insulin were generally well maintained (except in the starve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2
5

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 21 publications
2
58
2
5
Order By: Relevance
“…Similarly, the alanine and glutamine concentration in the artery (29.8 vs.28.8%) declined more than that in the vein (12.3 vs. 19.1%) and muscle compartments (4.1 vs. 4.7%). Human and animal studies have suggested that the muscle glutamine pool positively influences protein synthesis (24,27). Furthermore, it is claimed that this correlation is specific for glutamine and has not been observed with any other amino acid (32).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the alanine and glutamine concentration in the artery (29.8 vs.28.8%) declined more than that in the vein (12.3 vs. 19.1%) and muscle compartments (4.1 vs. 4.7%). Human and animal studies have suggested that the muscle glutamine pool positively influences protein synthesis (24,27). Furthermore, it is claimed that this correlation is specific for glutamine and has not been observed with any other amino acid (32).…”
Section: Discussionmentioning
confidence: 99%
“…It is a major gluconeogenic precursor [14,23], and a major 'fuel' for tissues with a high cell turnover rate (gut, immune system) [6]. It also plays a central role in the regulation of protein turnover [19]. In fact, we have previously shown that a doubling of the plasma glutamine concentration was associated with a significant increase in protein synthesis estimates [ 10,12].…”
Section: / Musclementioning
confidence: 99%
“…Since these studies have been performed in the postpubertal male after years of exposure to their endogenous sex hormones, it is difficult to extend their physiological implications to the events at pu- berty, when the body is exposed to androgenic hormones after more than a decade ofvery low exposure. Recent animal experiments have revealed a strong correlation between the size of the muscle free glutamine pool (the most abundant amino acid in the body) and the rate of protein synthesis in vivo ( 18,19). Other studies suggest that glutamine per se may stimulate protein synthesis, and that the size of the available free glutamine pool in muscle may be an index of protein accretion (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%